MODELING USER SATISFACTION OF MEDICAL EDUCATIONAL SERVICES - STOICA, Ivona; RADU, Anamaria Cătălina; DOBRESCU, Andra (Annales Universitatis Apulensis Series Oeconomica; Vol 1 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
This study aims to create a conceptual model for users satisfaction of medical educational services who attended the training professional sessions in the project called ”Professional training for implementing new technologies in the health care system." The results of the research obtaind from the multivariate analysis on user satisfaction of medical educational services was conceptualized and testedby creating a model to identify the main factors that influence the participants' satisfaction. The main factors that define the conceptual model are quality medical education, medical utility of the provided information, the location where the professional medical education training sessions were developed, and the control effects such as graduate institution prestige, respondents' age, medical specialty, number of years of practice of the medical specialty. To test the model, data were operated and analyzed using the IBM SPSS Statistics 20.